Membangun Desa Berkelanjutan: Pendampingan Pengelolaan Database Terintegrasi: Building Sustainable Villages: Integrated Database Management Assistance - Eko Jokolelono; Nurnaningsih Nurnaningsih; Muhammad Ichsan; Ahmad Syatir; Ika Rafika; Rita Suirlan; Nuryana Haprin Dj. Achmad; Meity Ferdiana Paskual; Indah Christiani; Nurul Rahma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Integrated database management is a fundamental prerequisite for promoting sustainable, transparent, and evidence-based village development. However, Sidondo IV Village faces significant challenges due to limited digital literacy and insufficient capacity among village officials and community members in utilizing data for development planning. This community service program aims to strengthen local capacity through workshops and hands-on assistance in managing integrated village databases using Microsoft Office–based spreadsheet applications. A participatory approach was employed, consisting of workshops on sustainable village development, technical training in data processing, and guided preparation of data collection instruments. Program effectiveness was evaluated using pre-test and post-test assessments administered to training participants. The results indicate a substantial improvement in participants’ digital literacy and data management skills, with average scores increasing from 47.37 to 82.50, representing a 74.16 percent improvement. The program successfully produced an integrated village database system to support the planning, implementation, and evaluation of village development programs. Overall, this initiative contributes to strengthening participatory, transparent, and sustainable village governance through data-driven decision-making.